"I'm Known": Building Relationships and Helping Students Construct Counternarratives on the West Side of Chicago. Issue 1 (September 2017) - Anderson, Luke
In discussing the intersection of education and poverty, we often lose sight of what it is actually like to teach or study in an urban school. What drives our most disadvantaged students? How can teachers measure success when schools lack the resources necessary to make lasting change in the community? From the perspective of an English teacher at a public charter high school in Chicago, I explore what it means to be a student and an educator in one of the most racially segregated and violent urban communities in the country. I argue that students' identities must be understood and affirmed before learning can occur. Educators who love students unconditionally and establish trust can help them to construct counternarratives about themselves and their communities to help them succeed in school. The neglect, violence, and social isolation experienced by children in many high poverty neighborhoods in Chicago pose a unique challenge for educators. Schools lack adequate resources to help the majority of their students succeed academically. Given the inequitable distribution of resources among schools in a state like Illinois, some teachers must find alternative paths to show students that they have value and can use their education to empower themselves.